2022
DOI: 10.3390/ijms23179841
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structures, Inhibitors, and Improvement Strategies of Glucose Oxidase

Abstract: Glucose oxidase, which uses molecular oxygen as an electron acceptor to specifically catalyze the conversion of β-d-glucose to gluconic acid and hydrogen peroxide (H2O2), has been considered an important enzyme in increasing environmental sustainability and food security. However, achieving the high yield, low price and high activity required for commercial viability remains challenging. In this review, we first present a brief introduction, looking at the sources, characteristics, catalytic process, and appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 110 publications
1
4
0
Order By: Relevance
“…The corresponding fit of the experimental data ( Figure 5 and Figure 6 ) seems satisfactory for both enzymes, in spite of the underlying naïve kinetic model that is much simpler than the literature reports [ 15 , 16 , 17 , 18 , 19 ]. The model also accounts for the observed larger extent of the [O 2 ] decay for the larger enzyme concentration ( Figure 4 ) and for the correlation between ([O 2 ] i − [O 2 ] e ) and p i (O 2 ) ( Figure 7 ).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The corresponding fit of the experimental data ( Figure 5 and Figure 6 ) seems satisfactory for both enzymes, in spite of the underlying naïve kinetic model that is much simpler than the literature reports [ 15 , 16 , 17 , 18 , 19 ]. The model also accounts for the observed larger extent of the [O 2 ] decay for the larger enzyme concentration ( Figure 4 ) and for the correlation between ([O 2 ] i − [O 2 ] e ) and p i (O 2 ) ( Figure 7 ).…”
Section: Resultssupporting
confidence: 54%
“…In particular, it was shown that the Glucox immobilized on the film’s surface shows tenfold higher activity than the enzyme present within the polymer matrix, although its capacity for total oxygen removal was lower than the enzyme immobilized on the film’s surface [ 7 ]. Glucox has found broad and satisfactory uses in preserving perishable products, in particular when coupled with enzymes capable of decomposing its hydrogen peroxide byproduct (such as catalase), or using hydrogen peroxide as a reagent for further oxidation steps (such as peroxidases) [ 4 , 13 , 14 , 15 ]. The presence of either of these “secondary” enzymes also minimizes the inhibiting effects of H 2 O 2 on the activity of Glucox [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Bio-Fenton remediation processes, the hydrogen peroxide necessary to activate the Fenton reaction is mainly provided by an enzymatic reaction catalyzed by Glucose Oxidase (GOx) that occurs in mild pH conditions. GOx is a stable oxidoreductase able that use oxygen as an electron acceptor to catalyze β-dglucose to d-glucono-δ-lactone by using the coenzyme FAD (Flavin Adenine Dinucleotide) as an electron carrier [181]. The oxidation of β-d-glucose leads to the reduction of one FAD molecule to the hydrogenated form FADH 2 ; successively, d-glucono-δ-lactone is nonenzymatically hydrolyzed to gluconic acid and the reduced coenzyme is re-oxidized to FAD by a molecule of dioxygen, producing a molecule of H 2 O 2 for each reaction cycle, as in Figure 6.…”
Section: Enzyme-driven Processes 221 Glucose-oxidase-based Bio-fentonmentioning
confidence: 99%
“…In 1999, the structure of glucose oxidase from Aspergillus was confirmed, which determined that GOx consists of two uniform subunits and that both subunits contain two separate domains: one is not covalently bound with FAD and the second attaches to the substrate. Structurally, the first domain is mainly a β-sheet and the second domain consists of four α-helices and an antiparallel β-sheet [6,7]. GOx is an enzyme that is considered an "ideal enzyme".…”
Section: Glucose Oxidase (Gox)mentioning
confidence: 99%